2013
DOI: 10.4103/2319-4170.110400
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biofilms in Endodontic Infections: An Update Review

Abstract: Biofilms and microbial aggregates are the common mechanisms for the survival of bacteria in nature. In other words, the ability to form biofilms has been regarded as a virulence factor. Microbial biofilms play an essential role in several infectious diseases such as pulp and periradicular pathosis. The aim of this article was to review the adaptation mechanisms of biofilms, their roles in pulpal and periapical pathosis, factors influencing biofilm formation, mechanisms of their antimicrobial resistance, models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 85 publications
(121 reference statements)
0
50
0
3
Order By: Relevance
“…The main challenges to the immune system are: recognizing the reabsorption. 28 It has been demonstrated that LPS also induces the expression of the adhesion molecules of leukocytes in endothelial cells and stimulates osteoclast differentiation and bone resorption, particularly through interactions with the receptor TLR-4 in cells of osteoblastic lineage 3 .…”
Section: Role Of Lps Binding Protein (Lbp) and The Cd14 Receptor In Cmentioning
confidence: 99%
See 4 more Smart Citations
“…The main challenges to the immune system are: recognizing the reabsorption. 28 It has been demonstrated that LPS also induces the expression of the adhesion molecules of leukocytes in endothelial cells and stimulates osteoclast differentiation and bone resorption, particularly through interactions with the receptor TLR-4 in cells of osteoblastic lineage 3 .…”
Section: Role Of Lps Binding Protein (Lbp) and The Cd14 Receptor In Cmentioning
confidence: 99%
“…After the development of aerobic and facultative anaerobic bacteria, a polymicrobial infection sets inside the root canal, where, with time, the Gramnegative and anaerobic species predominate 1,3 .…”
Section: Etiology Of Periapical Lesions and The Role Of Endotoxin In mentioning
confidence: 99%
See 3 more Smart Citations